UJI PROKSIMAT DAN EFEKTIVITAS TAPE HANJELI SEBAGAI ANTIBAKTERI STAPHYLOCOCCUS AUREUS PENYEBAB PENYAKIT KULIT - Haryani, Tri Saptari; Sudrajat, Cecep; Fauziah, Salsabela Sipa (Universitas Pakuan, 2023)
Indonesia is rich in various kinds of traditional fermented foods that can be developed into functional foods, one of which is tape hanjeli. Tape hanjeli is a traditional food typical of the Sukabumi region, West Java, made from hanjeli seeds (Coix lacyma jobi-L) which are fermented using tape yeast. The research aims to test the proximate content and effectiveness of hanjeli tape as an antibacterial for Staphylococcus aureus which causes skin infections. Research methods include making hanjeli tape, testing the proximate content and testing the effectiveness of hanjeli tape as an antibacterial for Staphylococcus aureus (Kirby-bauer). Data analysis was carried out qualitatively and quantitatively. From the results of the proximate content test, the ash content was 0.18%, protein 8.37%, fat 7.85%, carbohydrates 22.45%. The effectiveness test results obtained inhibition zones at concentrations of 60% (1.02 mm), 70% (3.56 mm), 80% (3.06 mm) 90% (5.68 mm). The conclusion of the research stated that hanjeli tape can act as a functional food and is effective as an antibacterial for Staphylococcus aureus which causes skin disease at a concentration of 90% of 5.68 mm and is included in the moderate inhibition zone category.